Influence of thiobencarb and butachlor on ribonuclease and deoxyribonuclease activity in seedlings of rice (Oryza sativa) and watergrass (Echinocloa crus-galll) - Kumar, Jitendra; Prakash, Jai (The Indian Journal of Agricultural Sciences, 2012)
A laboratory experiment was conducted during 1989 to study influence of thiobencarb and butachlor (each 0, 25, 50 and 75 ppm) on the activity of ribonuclease and deoxyribonudease in seedlings of rice (Oryza sativa L.) and watergrass [Echinocloa crus-galli (L.) P. Beauv.]. Seeds of rice and watergrass were placed on filter-paper in different petri-dishes containing 5 ml solution of different concentrations separately. To study the activity of ribonuclease and deoxyribonuclease the samples were taken at 24, 48, 72 and 96 hr after treatment. Both the herbicides reduced the activity of ribonuciease in treated seedlings of both the species. However, it was maximum at 72 hr after treatment in rice and 24 hr after treatment in watergrass, indicating faster growth in the latter. Deoxyribonuclease activity increased in rice but was not affected in watergrass. Maximum activity of deoxyribontlclease in rice was observed at 96 hr after treatment.